Flexoelectric Control of Defect Formation in Ferroelectric Epitaxial Thin Films. (22nd May 2014) - Lee, Daesu; Jeon, Byung Chul; Yoon, Aram; Shin, Yeong Jae; Lee, Myang Hwan; Song, Tae Kwon; Bu, Sang Don; Kim, Miyoung; Chung, Jin‐Seok; Yoon, Jong‐Gul; Noh, Tae Won
<x xml:space="preserve">Abstract</x> Flexoelectric control of defect formation and associated electronic function is demonstrated in ferroelectric BiFeO3 thin films. An intriguing, so far never demonstrated, effect of internal electric field (Eint) on defect formation is explored by a means of flexoelectricity. Our study provides novel insight into defect engineering, as well as allows a pathway to design defect configuration and associated electronic function. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>